Spinning the cultural tale: multiculturalism in K. S. Maniam's top winner - Mohd. Azrul, Mohd. Ezamir Azral; Mohd Ramli, Aimillia (Faculty of Languages and Communication, Universiti Sultan Zainal Abidin (UNISZA), 2015)

(untitled)
This paper analyses K. S. Maniam’s children’s novel, Top Winner (2005), in order to show how the narrative illustrates multiculturalism as instrumental in educating readers to respond positively to Malaysia’s cultural dynamism and heritage. It argues that Maniam’s fictional narrative recaptures the country’s multicultural roots through several themes, namely the kampung or the village, the cultural activity of gasing or the top and adat or tradition. In Maniam’s narrative, the village is seen as the propagator and guardian of communal values that inspire a sense of unity and peace amongst people. This paper also discusses the top, a traditional sport in Malaysia, in relation to the village in order to show how culture, through the art of top spinning and top making, acts like a rite of passage to manhood for the young, as well as the manifestation of the Malay idea of semangat (spirit). Adat, on the other hand, very much revolves around how one behaves, either at the personal level or the societal level. This theme is also considered alongside the role of the elderly in conveying knowledge and wisdom to their youngsters, as well as the co-dependency between adat and the shame culture. The novel also engages with the question of gender, and how it is related to the community. Finally, this paper makes use of the contemporary realism genre in its narration of the tale. This genre choice is a significant consideration as it draws upon realistic elements in its portrayal of Malaysia’s multicultural setting, including how the traditional and the modern fare against one another with regards to the preservation of cultural activities like the top. All these elements, we argue, encourage readers to ponder on the importance of cultural appreciation and preservation.